Assembly and alignment of long carbon nanotube bridges using thickness-controlled airflow-assisted dielectrophoresis for sensor applications - Abdulhameed, Abdullah Abdulhameed Gumaan (2021)
Carbon nanotubes (CNTs) have recently attracted significant interest due to their unique combination of properties, including high mechanical strength, distinct optical characteristics, and high thermal and electrical conductivity, which make them suitable for a wide range of applications. In order to apply CNT in devices, they have to be aligned and placed precisely in a location within the device. Examples of such devices are sensors, biosensors and transistors. In sensor devices, the aligned CNT transport the charge carriers faster than random CNT, which amplifies the sensor response. Currently, the main challenge in manufacturing CNT-based devices is the inability to precisely control the CNT placement in the desired location. Dielectrophoresis (DEP) is a method that can be applied to assemble and align CNT across electrode structures with great precision. However, the DEP method is limited to small-scale fabrication and fails to assemble CNTs across wide electrode gaps (>50μm) due to the presence of the Electric Double Layer (EDL) and Joule Heating effects. These effects cause medium drag velocity, which moves the CNTs away from the deposition area. Furthermore, there are difficulties in maintaining the alignment quality of long CNT bridges during the fabrication process, which reduces the reproducibility in manufacturing CNT-based devices. In this thesis, a new DEP setup is introduced that is able to minimize the medium drag velocity and preserve the quality of the aligned CNT bridges during assembly and alignment. The setup is based on the standard DEP setup with two mean differences: first is the ability to control the channel height through a top glass cover to minimize the medium drag velocity caused by Joule Heating and EDL effects, and second is the use of hot airflow to preserve the alignment quality during the drying process. In addition to these two modifications, a computational framework based on the Finite Element Method (FEM) is employed to find the ideal combination of the signal parameters and medium properties that result in minimum Joule Heating and EDL effects. Experimental work focusing on fabrication of electrode structures, preparation of CNT suspensions and design controllable signal supply system was carried out to prove that the effects of Joule Heating and EDL can be minimized to allow for a longer alignment of CNTs. The proposed system is able to align CNT bridges with lengths up to 125μm when using a sine wave signal of 20 volts peak to peak and 2.5MHz. The aligned CNT bridges are formed across Interdigitated Electrodes (IDE) made of Indium Tin Oxide (ITO) material because it is suitable for transparent sensors. We also fabricated three sensor devices: pH sensor, Hydrogen sensor, and temperature sensor using the new DEP setup. The response of the aligned CNT bridges towards the pH value, temperature variation, and Hydrogen molecules is measured and analyzed. The sensitivity of the aligned CNT toward the pH value of a solution is between 170% (pH=4) to 2000% (pH=10) and response times between 4 to 6 seconds. The temperature coefficient of the aligned CNT bridges after the assembly is -0.19572%, where the resistance increased from 550Ω to 575Ω when the temperature is reduced from 70oC to 30oC. The aligned CNT bridges are also exposed to Hydrogen gas at different concentrations. The sensitivity of the Hydrogen sensor is different based on the functional groups attached to the CNTs and the gas concentration. The experimental results show that the newly proposed DEP setups are able to precisely align CNTs more than 50% longer than the conventional DEP setup, and the produced CNT bridges are suitable for use in the fabrication of electronic devices.